Recognition of comprehensive income in Slovak companies - Lapková, Marta; Stašová, Jana (Buhalterinės apskaitos teorija ir praktika, 2014)
Financial statements are the key resource for assessing a company´s performance. The form and content of financial statements reflect a country`s accounting regulations. If financial statements can be drawn up under a range of different principles and procedures, this may cause problems for external users. The purpose of this paper is to evaluate comprehensive income recognition in the financial statements of Slovak companies that are prepared according to IFRS, with an emphasis on items of other comprehensive income.